2018
DOI: 10.20463/jenb.2018.0001
|View full text |Cite
|
Sign up to set email alerts
|

Association of exercise-induced autophagy upregulation and apoptosis suppression with neuroprotection against pharmacologically induced Parkinson's disease

Abstract: [Purpose]We investigated whether treadmill exercise (TE)-induced neuroprotection was associated with enhanced autophagy and reduced apoptosis in a mouse model of pharmacologically induced Parkinson's disease (PD).[Methods]PD was induced via the administration of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP). C57BL/6 male mice were randomly assigned to the following three groups: control (C57BL, n=10), MPTP with probenecid (MPTP/C, n=10), and MPTP/ C plus exercise (MPTP-TE, n=10). The MPTP-TE mice perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Those factors were all downregulated in the PD mice group while reversed in the exercise group. Therefore, physical exercise relieve PD symptoms in multiple ways, such as the autophagic ability promotion of the cells [183] and mitochondrial function enhancement.…”
Section: Physical Exercise Can Enhance Mitochondrial Functionmentioning
confidence: 99%
“…Those factors were all downregulated in the PD mice group while reversed in the exercise group. Therefore, physical exercise relieve PD symptoms in multiple ways, such as the autophagic ability promotion of the cells [183] and mitochondrial function enhancement.…”
Section: Physical Exercise Can Enhance Mitochondrial Functionmentioning
confidence: 99%
“…It has been postulated that regular physical exercise can promote a beneficial effect on the health of individuals and is considered an important autophagic inducer ( 180 183 ). It was observed that treadmill exercise (8 weeks) in mice modulated the levels of autophagy-associated proteins, including Beclin1, and improved autophagy ( 184 ). Based on literature data, it is suggested that physical exercise can induce autophagy through the following mechanism: exercise induces decreased adenosine triphosphate/adenosine monophosphate (ATP/AMP) in the cell, and this induces AMP-activated protein kinase (AMPK) activation; AMPK activation promotes inhibition of mammalian target of rapamycin (mTOR), leading to Unc-51 kinase 1 (ULK1) disinhibition, which is also phosphorylated and activated by AMPK; the ULK1 complex induces activation of the Phosphatidylinositol 3-kinase (PI3K) complex culminating in increased expression of autophagy-related proteins (Atgs); AMPK also promotes activation of autophagy-related transcription factors such as forkhead box O (FOXO), thereby increasing the expression of LC3-II and Atgs [for more detailed information on these signaling pathways, see ( 172 , 185 , 186 ) ( Figure 3B )].…”
Section: Influence Of Physical Exercise In the Autophagy Process In Amentioning
confidence: 99%
“…Additionally, PA can take part in brain functions by improving mood, mental health, and cognitive activity by immune system-mediated effects [ 8 ]. Additionally, regular and moderate physical activity maintains the activation of glial cells within a healthy range, which may reduce or delay the progression of brain neurodegeneration [ 9 14 ].…”
Section: Introductionmentioning
confidence: 99%